Early and Late Postnatal Accelerated Growth Have Distinct Effects on Metabolic Health in Normal Birth Weight Infants - Zhang, Dan-Li; Du, Qinwen; Djemli, Anissa; Julien, Pierre; Fraser, William D.; Luo, Zhong-Cheng (Frontiers in Endocrinology, 2017)
ABSTRACT Accelerated growth in postnatal life in low birth weight infants has been associated with insulin resistance and metabolic syndrome related disorders in later life. Postnatal accelerated growth in also common in normal birth weight infants, but little is known about the impact on metabolic health. In a prospective cohort study of 203 term normal birth weight infants, we evaluated the impacts of accelerated (ΔWeight Z score >0.5) or decelerated (ΔWeight ΔZ <-0.5) growth during early (0-3 months) and late (3-12 months) postnatal life on metabolic health indicators at age 1-y. The primary outcomes were homeostasis model assessment of insulin resistance (HOMA-IR), β-cell function (HOMA-β) and fasting plasma lipids. Adjusting for maternal, paternal and infant characteristics, accelerated growth during the first 3 months of life was associated with a 41.6% (95% confidence interval 8.9-84.2%) increase in HOMA-β, and a 8.3% (0.7-15.4%) decrease in fasting plasma total cholesterols, and was not associated with HOMA-IR in infants at age 1-y. Accelerated growth during 3-12 months was associated with a 30.9% (3.3-66.0%) increase in HOMA-IR, and was not associated with HOMA-β. Neither accelerated nor decelerated growth was associated with fasting plasma triglycerides, HDL or LDL cholesterol concentrations in infants at age 1-y. Accelerated growth during early postnatal life may be beneficial for β-cell function, but during late postnatal life harmful for insulin sensitivity in normal birth weight infants.